Nilai - Nilai Tasawuf dalam Manajemen Air Minum MaDa di Yayasan Pondok Pesantren Ahlus Shafa Wal Wafa: Studi Prinsip Syafi'i dan Implementasi Giti – Gito - Intan Nuraini; Wahdah Wahdah; Muflih Muflih (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study investigates the incorporation of Sufi-oriented values into the management practices and production processes of MADA Drinking Water operated by the Ahlus Shafa Wal Wafa Islamic Boarding School Foundation. The research focuses on the Syafi’i ethical concept known as Giti–Gito, which encompasses spiritual and moral values including sincerity, patience, inner richness, holistic physical and spiritual well-being, as well as fairness in sharing resources. The main aim of this study is to examine how these values are implemented within pesantren-based business management and to assess their impact on employees’ work attitudes, leadership styles, and interpersonal relations in the workplace. This research employs a qualitative case study method. Data were gathered through semi-structured interviews, participant observation, and a review of relevant institutional documents. The findings reveal that the implementation of Giti–Gito values has successfully shaped a work environment grounded in religious ethics, social harmony, and humanistic principles. The Giti aspect strengthens employees’ commitment to sincerity, patience, and accountability in carrying out their responsibilities, while the Gito aspect contributes to enhancing employee welfare and fostering a sense of social responsibility. Although challenges remain in reconciling spiritual values with modern management demands, the integration of both spiritual and professional dimensions has demonstrated its effectiveness in creating a productive, ethical, and sustainable organizational environment.